A Decentralized Control of Cascaded-Type AC Microgrids Integrating Dispatchable and Nondispatchable Generations - Lang Li; Peng Tian; Genglong Yan; Shixun Shen (International Transactions on Electrical Energy Systems, 2024)
Existing studies on decentralized control of islanded cascaded-type AC microgrids mainly focus on either dispatchable or nondispatchable DGs. However, islanded cascaded-type AC microgrids may contain both types of DGs. To address this issue, a decentralized control scheme is proposed that integrates both dispatchable and nondispatchable DGs for the islanded cascaded-type AC microgrids. By performing this method, frequency synchronization and power factor angle consistency for all DGs are obtained in a communication-free manner. One dispatchable DG is regulated to maintain constant voltage amplitudes at the point of common coupling (PCC). A high-quality power supply for load demands is achieved. Meanwhile, the nondispatchable DG is controlled to output active power based on its available capacity for using renewable energy efficiently. Next, a stability analysis of the proposed control for the cascaded-type AC microgrids is performed. Finally, simulations and experiments are executed to showcase the efficacy of the proposed scheme.